Moby Dick - Herman Melville (Wordsworth Editions Limited, 1993)
Mpby Dick is the story of Captain Ahab's quest to avenge the whale that reaped his leg. the quest is an obsession and the novel is a diabolical study of how a man becomes a fanatic.